About the speaker towards a syntax of indexicality - Giorgi, Alessandra (Oxford : Oxford University Press, 2010)
Alessandra Giorgi considers the semantic and syntactic nature of indexicals: linguistic expressions whose reference shifts from utterance to utterance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Indexicals (Semantics)